도시지표특성 모수 적용을 통한 태양복사모델 개선 효과 분석 - 양호진(Yang, Hojin); 권혁기(Kwon, Hyuk-Gi); 이채연(Yi, Chaeyeon) (한국기후변화학회지, 2022)
Sudden change in an urban thermal environment has an intimate effect on resident’s daily life, prompting increased interest in and demand for improvement of urban thermal environments. In order to improve the urban thermal environment, heat vulnerability information that reflects the actual physical environment is needed in a format that can be controlled as spatial information. In addition, a quantitative method is need to analyze heat stress, as experienced by urban residents. In this study, solar radiation flux simulation results for Seoul metropolitan’s main residential and commerce area are analyzed, and the accuracy of these results is enhanced by improving the urban simulation index. The SOLWEIG model is used in this study as it can simulate high-resolution solar radiation flux and mean radiant temperature using data such as the sky view factor, reflecting shapes of buildings and vegetation, shadow pattern, temperature, humidity, and solar radiation. In order to reflect domestic condition and geographical characteristics, a correlation equation of solar altitude angle and the difference in surface temperature and atmospheric temperature by land cover is derived. Based on this, a comparative analysis is performed on the simulation result using the SOLWEIG model and solar radiation observation data. KCI Citation Count: 0